An androgen receptor negatively induced long non-coding RNA ARNILA binding to miR-204 promotes the invasion and metastasis of triple-negative breast cancer. Issue 12 (December 2018) - Yang, Fang; Shen, Yan; Zhang, Wenwen; Jin, Juan; Huang, Doudou; Fang, Hehui; Ji, Wenfei; Shi, Yaqin; Tang, Lin; Chen, Weiwei; Zhou, Guohua; Guan, Xiaoxiang
Abstract Androgen receptor (AR) is emerging as a novel prognostic biomarker in triple-negative breast cancer (TNBC), but the underlying mechanisms remain unknown. As accumulating evidence has shown that long non-coding RNAs (lncRNAs) regulate important cancer hallmarks, we hypothesised that AR-regulated lncRNAs might play roles in TNBC progression. Here, we performed experiments with or without DHT treatment in three TNBC cell lines, and we identified an AR negatively induced lncRNA (ARNILA), which correlated with poor progression-free survival (PFS) in TNBC patients and promoted epithelial−mesenchymal transition (EMT), invasion and metastasis in vitro and in vivo. Subsequently, we demonstrated that ARNILA functioned as a competing endogenous RNA (ceRNA) for miR-204 to facilitate expression of its target geneSox4, which is known to induce EMT and contribute to breast cancer progression, thereby promoting EMT, invasion and metastasis of TNBC. Our findings not only provide new insights into the mechanisms of lncRNA in regulating AR but also suggest ARNILA as an alternative therapeutic target to suppress metastasis of TNBC patients.